2007
DOI: 10.1177/0261927x06296428
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Common Ground on How Speakers Use Gesture and Speech to Represent Size Information

Abstract: Past research has investigated the impact of mutual knowledge on communication by focusing mainly on verbal communication. This study uses a wider focus, which includes speech and gesture. Speakers completed a referential communication task with recipients who did or did not share with them knowledge about the size of certain entities. The results showed that when such common ground exists between interlocutors, speakers' use of gesture and speech is affected. The main finding was that when speakers talked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
99
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(110 citation statements)
references
References 37 publications
6
99
2
3
Order By: Relevance
“…A qualitative analysis of a number of gestures confirmed that gesture parts depicting new information were larger and more precise (Gerwing & Bavelas, 2004, p. 182). Holler and Stevens (2007) obtained similar results in a referential communication task. They asked participants to locate targets in Where's Wally?…”
Section: Reduction In Gesturesupporting
confidence: 60%
See 2 more Smart Citations
“…A qualitative analysis of a number of gestures confirmed that gesture parts depicting new information were larger and more precise (Gerwing & Bavelas, 2004, p. 182). Holler and Stevens (2007) obtained similar results in a referential communication task. They asked participants to locate targets in Where's Wally?…”
Section: Reduction In Gesturesupporting
confidence: 60%
“…In addition, we know from various studies that repeated references can be reduced acoustically as well, in such a way that, for example, the second realisation of the word ''building'' in our example may be less intelligible (when heard in isolation) than the initial one (e.g., Aylett & Turk, 2004;Bard et al, 2000;Fowler, 1988). Finally, and most importantly for the current study, a number of studies have shown that repeated references are also accompanied by fewer gestures (e.g., de Ruiter, Bangerter, & Dings, 2012;Holler & Stevens, 2007;Holler, Tutton, & Wilkin, 2011;Levy & McNeill, 1992).…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…This is one instance of audience design (Clark & Carlson, 1982), in which utterances are constructed according to what others in the communicative exchange know and believe (Clark, 1996). Audience design has been reported in speech and actions in both naturalistic and experimental settings (Holler & Stevens, 2007;Jacobs & Garnham, 2007;O'Neill, Bard, Linnell, & Fluck, 2005;Ozyurek, 2002), but there is still considerable debate over when, how, and why it is used. An outstanding issue is whether audience design is structurally linked to initial attempts to communicate, or whether it is used parsimoniously to repair erroneous attempts.…”
Section: Introductionmentioning
confidence: 99%
“…It has been repeatedly shown that our communicative actions are selected according to what we believe addressees of a communicative interaction know and believe [audience design, (Clark, 1996;Holler & Stevens, 2007;Jacobs & Garnham, 2007;O'Neill, Bard, Linnell, & Fluck, 2005)]. For instance, adults tend to modify their speech, gestures, and accompanying body motions when addressing a child (Brand, Baldwin, & Ashburn, 2002;Brodsky, Waterfall, & Edelman, 2007;Grieser & Kuhl, 1988;O'Neill, et al, 2005;Warrenleubecker & Bohannon, 1984).…”
Section: Introductionmentioning
confidence: 99%